Oral peptide and protein delivery: intestinal obstacles and commercial prospects. (August 2014) - Smart, Alice L; Gaisford, Simon; Basit, Abdul W
<x xml:space="preserve">Abstract</x> Introduction: Pharmaceutical research and development is increasingly focussed on biopharmaceuticals including peptide and protein drugs. Despite their growing importance and almost 100 years of research, the vast majority are still only available by injection. Oral bioavailabilities of peptide and protein drugs are very low mainly because of the stability and permeability barriers of the gastrointestinal (GI) tract. Areas covered: Data from studies of peptide/protein drug oral bioavailability, stability and permeability in the stomach, small intestine and large intestine have been compiled to make comparisons between the various regions of the GI tract and peptides/proteins with differing characteristics. Assessment of the oral formulation strategies that have progressed farthest in clinical trials has been conducted to identify which have the best potential for future success. Expert opinion: Oral delivery of peptides and small proteins is increasingly achieved by utilising formulations that combat the stability challenges of the GI tract and disrupt the intestinal cell membranes to enable absorption. However, oral bioavailabilities remain low and variable therefore high, potentially toxic doses of peptide/protein drugs are needed to elicit a therapeutic effect leading to high cost of the final product. There is very little research into larger proteins, making their oral delivery unlikely in the near future.